Aligning seminars with Bologna requirements: reciprocal peer tutoring, the solo taxonomy and deep learning. Issue 9 (1st September 2016) - Lueg, Rainer; Lueg, Klarissa; Lauridsen, Ole
Abstract : Changes in public policy, such as the Bologna Process, require students to be equipped with multifunctional competencies to master relevant tasks in unfamiliar situations. Achieving this goal might imply a change in many curricula toward deeper learning. As a didactical means to achieve deep learning results, the authors suggest reciprocal peer tutoring (RPT); as a conceptual framework the authors suggest the SOLO (Structure of Observed Learning Outcomes) taxonomy and constructive alignment as suggested by Biggs and Tang. Our study presents results from the introduction of RPT in a large course. The authors find that RPT produces satisfying learning outcomes, active students, and ideal constructive alignments of the seminar content with the exam, the intended learning outcomes, and the requirements of the Bologna Process. Our data, which comprise surveys and evaluations from both faculty and students, suggest that RPT fosters deeper learning than does teacher-led instruction. Based on these findings, the authors also offer guidelines regarding how to implement RPT and how to overcome barriers.